The Albanese government has committed to enshrining a First Nations Voice in the Constitution. What do Australians think of the idea? - Jacob Deem; Adrian Miller; AJ Brown; Susan Bird (2022)
Prime Minister Anthony Albanese and his new government have committed to enshrining a First Nations Voice in the Australian Constitution. To do so, a majority of Australians in a majority of states will have to vote “yes” at a referendum. But what are the other challenges along the way? Why might people support a Voice, or why might they be against it? Last year, CQUniversity and Griffith University conducted the Australian Constitutional Values Survey to answer these questions.